Perception of daycare center assistants and auxiliaries about the most recurring health injuries in children - Oliveira, Maraísa Ritiele Custódio Alves de; Moura, Jamille Neves Barbosa; Nascimento, Lais Cardoso do; Araújo, Lilhian Alves de; Camisão, Agnes Raquel; Cardoso, Camila; Mota, Elias Emanuel Silva (Revista Uningá, 2022)
The objective of the present study was to identify the diseases that affect the health of children who uses daycare centers in a municipality in Goiás inland, and to point out the conducts performed by the collaborators in early childhood education when detecting them. This is a quantitative, descriptive research, performed in public daycare centers. It was selected a probabilistic sample of daycare centers representing 50% of the institutions. The study population were the assistants and educational auxiliaries, because they are the employees who act directly in the children care. The data collection occurred in only one-step, by signing the ‘Free and Informed Consent Term’ (TCLE) and applying a semi-structured questionnaire, with open and closed questions. The CEP approved the study with the Opinion of Nº: 3.612.776. The Microsoft Excel software, version 2010 transcribed and stored the data. Then, descriptive analyses of the data were performed by using absolute frequency distribution (N) and relative frequency (%). The presence of such diseases was observed: influenza (90%), viruses (74%) and allergies (40%). The present study evidenced that there is an adequate and responsible conduct of the daycare center collaborators when they observe any problems in the children, registering the occurrences in a proper form for this purpose, they communicate the direction of the institution, as well as the parents and guardians, and, administer medication by updated medical prescription. It was concluded that it is of extremely importance the daycare centers maintain control regarding the existence and prevalence of diseases in enrolled and effective children, in order to create strategies for reducing them through health promotion, both for the children and for the collaborators themselves.